Kajian Filosofis Tradisi Mejukjukan Di Desa Adat Bengkala Kecamatan Kubutambahan Kabupaten Buleleng - Ni Putu Sinta Oktaviani; Ida Bagus Wika Krishna; Ayu Veronika Somawati (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2022)
Mejukjukan is a tradition that has been passed down from generation to generation by the Bengkala Indigenous village community which is believed to contain meaning that can be used as a way of life. The results obtained from this study are: 1).tradition mejukjukan in its implementation is based on a mythological basis, and foundation of public trust. 2). tradition mejukjukan divided into three stages, namely: the preparatory stage starting with the holding of tawur kesanga and prayer together, the core stage, namely the ngejuk, and the final stage is symbolically marked by the truni being crowned as Ratu Bengkala and the ogoh-ogoh parade. 3). The philosophical meanings contained in mejukjukan are: the meaning of respect for ancestors is reflected in the presence of the Ratu Bagus Temple which is located at the Dalem Temple of the Bengkala Traditional Village and the Ratu Ayu Mas Merenteng Temple which is placed at the Puseh Temple of Keladis Village; The meaning of glorification to women can be seen from the story behind this tradition where there is a woman who is mistreated by a man; The meaning of harmony in which there are aspects of parhyangan, aspects of pawongan, and aspects of palemahan; The meaning of education, namely character education, can be seen in the task of Ratu Bengkala who teaches or becomes an example for teenagers about how to dress properly and correctly when going to the temple.